Bank lending opportunities and credit standards - Güner, A. Burak (Journal of Financial Stability, 2008)
This article empirically tests the hypothesis that credit-screening standards can be first increasing and then decreasing in the quality of the bank's pool of potential borrowers, which in turn may vary through the business cycle or across different segments of the lending markets. A key implication is that banks with lending opportunities toward the middle of the quality spectrum can have loan portfolios that perform better than do the portfolios of banks with loan-origination opportunities that are either too weak or too strong. Using banks’ volume of secondary-market loan sales as a proxy for the richness of lending opportunities, I find an inverse U-shaped relation between the performance of banks’ loan portfolios and their activity in the loan sales market. The pattern deserves scrutiny for its policy implications, as many regulators hold the view that countercyclical variation in credit standards may have a destabilizing effect on business cycles.